Influence of sodium citrate and AgNO3 on the size of silver nanoparticles in PVA - Khoa, Nguyễn Cửu; Dư, Cao Văn (Vietnam Journal of Chemistry, 2012)
Silver/polyvinylalcohol nanocomposites are prepared via in situ reduction of silver salt by reducing agent – hydrazine hydrate (HH) and sodium citrate was used as supportive distribution agent. The solutions and the films are characterized by using UV-Vis, XRD and TEM. XRD patterns are consistent with that for cubic silver. TEM of the nanocomposite film shows particles distribution and size within the film.